BASIC LIFE SUPPORT FOR COVID-19 CONFIRMED PATIENTS WITH CARDIAC ARREST: LITERATURE REVIEW - Sepdianto, Tri Cahyo; Abiddin, Andi Hayyun; Irawan, Pungky Dwi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Recently, many cases require basic life support and have become the hottest news caused by Corona Virus Disease (Covid-19). Actions taken must be in accordance with existing guidelines and pay attention to rescuers. As part of human life support management actions, a nurse needs to think of strategies that can be done to save patients without being infected. This study was conducted to describe the management of living bedrock in patients with confirmed Covid-19 cardiac arrest. By using the keywords Basic Life Support, Cardiac Arrest and Covid-19 in the database for a literature review. This article is taken from a reputable or accredited database. 2 articles were taken from the journal of the American Heart Association, 1 article was obtained from PubMed, and the other 2 articles used the Google Scholar database. This selection was taken by paying attention to the PEOS framework, then the articles were analyzed one by one. The management of basic life support for patients with confirmed Covid-19 cardiac arrest can be carried out by observing the principles of basic life support in Covid-19 patients and the basic life support algorithm for cardiac arrest patients with confirmed Covid-19.